Histone Deacetylase 11 Knockdown Blocks Larval Development and Metamorphosis in the Red Flour Beetle, Tribolium castaneum - George, Smitha; Palli, Subba Reddy (Frontiers in Genetics, 2020)
Post-translational modifications (PTM) such as methylation, acetylation, phosphorylation, and ubiquitination of histones and other proteins regulate expression of genes. The acetylation levels of these proteins are determined by the balance of expression of histone acetyltransferase and histone deacetylases. We recently reported that class I HDACs (HDAC1 and HDAC3) play important roles in juvenile hormone (JH) suppression of metamorphosis in the red flour beetle, Tribolium castaneum. Here, we report on the function of a single class IV HDAC member, HDAC11. Injection of dsRNA targeting T. castaneum HDAC11 gene into newly molted last instar larvae induced knockdown of the target gene and arrested larval development and prevented metamorphosis into the pupal stage. Dark melanized areas were detected in larvae that showed developmental arrest and mortality. Developmental expression studies showed an increase in HDAC11 mRNA levels beginning at the end of the penultimate larval stage. These higher levels were maintained during the final instar larval and pupal stages. A JH analog, hydroprene, suppressed HDAC11 expression in the larvae. Sequencing of RNA isolated from control and dsHDAC11 injected larvae identified several differentially expressed genes, including those involved in JH action, ecdysone response, and melanization. The acetylation levels of core histones showed an increase in TcA cells exposed to dsHDAC11. Also, an increase in histone H3 acetylation, specifically H3K18 and H3K27, was detected in HDAC11 knockdown larvae. These studies report the function of HADAC11 in insects other than Drosophila for the first time and show that HDAC11 influences the acetylation levels of histones and expression of multiple genes involved in T. castaneum larval development.